Bridging the academia-to-industry gap: organ-on-a-chip platforms for safety and toxicology assessment. (September 2021) - Ching, Terry; Toh, Yi-Chin; Hashimoto, Michinao; Zhang, Yu Shrike
Abstract : Some organ-on-a-chip (OoC) systems for drug evaluation show better predictive capabilities than planar, static cell cultures and animal models. One of the ongoing initiatives led by OoC developers is to bridge the academia-to-industry gap in the hope of gaining wider adoption by end-users – academic biological researchers and industry. We discuss several recommendations that can help to drive the adoption of OoC systems by the market. We first review some key challenges faced by OoC developers before highlighting current advances in OoC platforms. We then offer recommendations for OoC developers to promote the uptake of OoC systems by the industry. Highlights: Several organ-on-a-chip (OoC) systems have been shown to recapitulate human physiology and pathology, and have demonstrated similar or better predictive ability for drug evaluation than static cellular cultures and animal models. Ongoing advances in the development of OoCs have emphasized the development of multi-organ platforms, termed 'human-body-on-a-chip', that establish physiologic flow between organs to produce organ–organ interactions and permit the analysis of interdependent pharmacokinetics, pharmacodynamics, and toxicokinetics/toxicodynamics relationships in vitro . In the past decade advances in OoC technology have led to several OoC/multi-OoC startup companies. Regulatory agencies have also launched initiatives to support the development of drug development tools including OoCs for regulatory use.